PRINCIPLES OF OPTIMIZATION OF MODES WORKS OF GAS PIPELINE - Грудз, Ярослав Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Principles of optimization of office hours of main gas pipelines and difficult gas-transport systems are resulted with the use of various criteria of optimum. The method of optimization of office hours GTS is offered in the conditions of transition to the market relations.